Subaxial Spine Fractures: A Comparison of Patient-reported Outcomes and Complications Between Anterior and Posterior Surgery. Issue 17 (1st September 2021) - Fröjd Révész, David; Norell, Andrea; Charalampidis, Anastasios; Endler, Peter; Gerdhem, Paul
Abstract : Study Design: Observational study on prospectively collected data. Objectives: The aim of this study was to compare long-term patient-reported outcomes and complications after anterior or posterior cervical spine surgery for subaxial fractures. Summary of Background Data: There is no consensus in the literature regarding the optimal surgical approach when treating spine fractures in the subaxial region. Methods: A total of 200 individuals who had been treated with either anterior or posterior surgery due to a subaxial single segment, or single vertebra, injury between 2006 and 2016 and had at least 1 year follow-up were identified in the Swedish Spine register. Cases were matched 1:1 for age (±5 years). Outcomes were Neck Disability Index (NDI) and EQ-5D-3L, and reoperations, mortality, and surgeon- and patient-reported wound complications within 90 days. t Tests and χ 2 tests were used statistical comparisons. Results: At follow-up, NDI was 23 (21) in the anterior group and 29 (21) in the posterior group ( P  = 0.07). EQ-5D-3L index was 0.62 (0.37) in the anterior group and 0.54 (0.39) in the posterior group ( P  = 0.13). Patient satisfaction was higher in the anterior group (89% vs. 73%, P  = 0.03). No deaths occurred within the first 90 days after surgery, six individuals in the anterior group and three individuals in the posterior group were reoperated ( P  = 0.31), and five individuals in the anterior group and 24 in the posterior group suffered a wound infection ( P  < 0.001). Conclusion: Anterior surgery and posterior surgery were associated with similar neck disability and general quality of life at follow-up, whereas anterior surgery was associated with higher patient satisfaction and lower infection rates. Level of Evidence: 3 Abstract : There is no consensus regarding the optimal surgical approach when treating spine fractures in the subaxial region. Anterior surgery and posterior surgery were associated with similar neck disability and general quality of life at follow-up, whereas anterior surgery was associated with higher patient satisfaction and lower infection rates.